THE EFFECT OF WORK MOTIVATION, WORK LOAD AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE OF PT. BARA BENTALA INDONESIA - Saputro, Galih Eko; Puspitasari, Devy Mawarnie (International Humanities and Applied Science Journal, 2025)
This study aims to examine the effect of work motivation, workload, and work discipline on employee performance at PT. Bara Bentala Indonesia. The research method used is a quantitative method with Partial Least Square (PLS) analysis tools. The population in this study was 40 employees of PT. Bara Bentala Indonesia using a quantitative descriptive approach. The sample of this study was all employees working at PT. Bara Bentala Indonesia. Determination of sample size using saturated samples, namely taking the entire population. The data collection method uses a survey method with a questionnaire as the research instrument. The results of the data processing show that work motivation has a significant and positive effect on employee performance and the work discipline variable has a significant and positive effect on employee performance. While the workload variable does not affect the performance of employees at PT. Bara Bentala Indonesia.  Keywords: Work Motivation, Work Load, Work Discipline, Employee Performance